Comparison of Sulfur Hexafluoride (SF6) and Air Tamponade in Noniridectomized Descemet Membrane Endothelial Keratoplasty. Issue 3 (March 2018) - Einan-Lifshitz, Adi; Sorkin, Nir; Boutin, Tanguy; Showail, Mahmood; Borovik, Armand; Jamshidi, Farzad; Chan, Clara C.; Rootman, David S.
Abstract : Purpose: To compare the efficacy and safety of 20% sulfur hexafluoride gas (SF6 ) and air tamponade in patients who underwent noniridectomized Descemet membrane endothelial keratoplasty (DMEK). Methods: A retrospective chart review of patients who underwent DMEK with either air or SF6 tamponade: 41 eyes received air tamponade (group 1) and 41 received SF6 tamponade (group 2). Best spectacle-corrected visual acuity, endothelial cell density, and complications including graft detachment and elevated intraocular pressure were compared. Results: The mean follow-up time was 8 ± 4 months in group 1 and 3 ± 2 months in group 2. Mean best spectacle-corrected visual acuity improved from 1.12 ± 0.88 to 0.64 ± 0.78 logarithm of the minimum angle of resolution (logMAR) in group 1 ( P = 0.009) and from 1.00 ± 0.78 to 0.62 ± 0.53 logMAR in group 2 ( P = 0.006). The graft detachment rate was 39% (16 eyes) in group 1 and 42% (17 eyes) in group 2 ( P = 0.822). The rate of graft detachment larger than one third of the graft area was 17% in group 1 and 20% in group 2 ( P = 0.775). Rebubbling was performed in 26.8% and 20% of eyes in group 1 and 2, respectively ( P = 0.43). Average endothelial cell loss was 32% in group 1 and 33% in group 2 ( P = 0.83). In the immediate postoperative period, elevated intraocular pressure was observed in 2 eyes (5%) in group 1 and in 4 eyes (10%) in group 2 ( P = 0.4). There was 1 primary graft failure in each group. Conclusions: Use of air with it being readily available and short acting is a good method of Descemet membrane tamponade in noniridectomized DMEK.